2006
DOI: 10.1094/cc-83-0340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micronization on Protein and Rheological Properties of Spring Wheat

Abstract: This research investigated the effects of micronization, at different moisture levels, on the chemical and rheological properties of wheat. A set of tests designed to analyze protein fraction characteristics and rheological behaviors were conducted on samples from four wheat cultivars (AC Karma, AC Barrie, Glenlea, and Kanata). After being subjected to infrared radiation at three moisture levels (as‐is, 16%, and 22%), the seeds were milled to produce straight‐grade flour. The protein fractionation test reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…The distribution of the proteins in the pre‐germinated flour were; ∼40% >30 kDa, 30% between 30 and 16 kDa and 30% <16 kDa. This is consistent with the report of Hsu et al () who also observed more small protein subunits after germination compared with the nongerminated (control) yellow pea and with Sun et al () who reported no differences in the electrophoretic profile of the control and micronized wheat sample. Lipoxygenase (97.2 kDa), convicilin (77.9–72.4 kDa), legumin (63.6 kDa; α: 40.8 kDa; β: 23.1–22.3 kDa), vicilin (47.3 kDa, 37–31.8 kDa, and 28.7 kDa) were observed in different pea bean varieties (Barac et al, ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The distribution of the proteins in the pre‐germinated flour were; ∼40% >30 kDa, 30% between 30 and 16 kDa and 30% <16 kDa. This is consistent with the report of Hsu et al () who also observed more small protein subunits after germination compared with the nongerminated (control) yellow pea and with Sun et al () who reported no differences in the electrophoretic profile of the control and micronized wheat sample. Lipoxygenase (97.2 kDa), convicilin (77.9–72.4 kDa), legumin (63.6 kDa; α: 40.8 kDa; β: 23.1–22.3 kDa), vicilin (47.3 kDa, 37–31.8 kDa, and 28.7 kDa) were observed in different pea bean varieties (Barac et al, ).…”
Section: Resultssupporting
confidence: 92%
“…The distribution of the proteins in the pre-germinated flour were; 40% >30 kDa, 30% between 30 and 16 kDa and 30% <16 kDa. This is consistent with the report of Hsu et al (1982) who also observed more small protein subunits after germination compared with the nongerminated (control) yellow pea and with Sun et al (2006)…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis supporting
confidence: 93%
See 1 more Smart Citation
“…However, a reduction in dough development time was reported. [46] The above studies clearly demonstrated that the disintegration of starch granules causes the reduction in values of pasting profile in all the IR treated grains and starches, except waxy varieties of barley indicating the importance of amylose in deciding the rheological properties. In addition to starch, the protein content also seemed to affect the rheological properties which might be the reason for the difference in the behavior of monocots and dicots to IR radiations.…”
Section: Rheological Propertiesmentioning
confidence: 69%
“…IR can be used for stabilization of rice bran as it was effective in retarding FFA increase during the course of storage. The effect of micronization on protein solubility characteristics of wheat having different gluten strength was elucidated by Sun et al [43]. Wheat grains were micronized after tempering to 16 and 22 % moisture content, and the performances were compared with that of grains not subjected to tempering.…”
Section: Micronization Of Cerealsmentioning
confidence: 99%